Egy mezőgazdasági vállalkozás beruházásának megtérülési vizsgálata - Litresits Andrea (2016)
The encouragement and development of agricultural ventures are advanced state objectives. Additional to national subventions also tenders of the European Union are avaliable for persons intending to enterprise. Due to the current, often unsecure position of the branch tasks related to planning and estimation of return play a significant role. The general objective of my essay is to introduce the start and the initial steps of the selected agricultural venture dealing with egg production, to investigate the source composition and return of the related green-field investment and to evaluate the short- and long-term economic relations of the venture. According to my assumption the investment is returning owing to the conscious planning process and the application of modern technologies within ten years for certain. For the realization of my general objective I have broken down the analysis in concrete steps. The internal capabilities (strengths, weaknesses) of the agricultural venture and the external conditions (opportunities, threats) were summarized by means of the method of swot-analysis. Because the self-effort of the venture was not sufficient for the execution of the investment, during the calculations I had to consider also the amounts resulting from Union-sources. Related to the EU-tender I have studied the feasibility of the condition system related to the fulfilment of the subvention awarded. In order to ensure the continuity of production I have investigated the conformity of the selected allowance for depreciation. Beyond the analysis of the short-term economic situation of the production and the social, economic, politic environment I have also performed the long-term economy investigation of the development, for which I have carried out dynamic investment-economy calculations (net present value calculation, dynamic rate of return, turnover rate, and internal rate of return). Based on the calculations it has been established that the realization of the venture has raison d’étre under current economic and financial circumstances. Based on the financial calculations the investment shall return already in the 8th year and afterwards even additional yields are to be expected. The internal rate of interest develops beyond the preliminary expectations. Although economy does not lack for difficulties and risks, the owner has appropriate action plan for turning them. The planned money flows ensure the capital required for the exchange of technology after obsolescence, which shows that the venture can be maintained for long term. A mezőgazdasági vállalkozások ösztönzése és fejlesztése kiemelt állami célkitűzés. Az állami támogatások mellett európai uniós pályázatok is a vállalkozni szándékozók rendelkezésére állnak. Az ágazat jelenlegi, sokszor bizonytalan helyzete miatt kiemelten fontos szerephez jutnak a tervezési és a megtérülés becslésével kapcsolatos feladatok. Dolgozatom általános célkitűzése a kiválasztott, tojástermeléssel foglalkozó mezőgazdasági vállalkozás indulásának és a kezdeti lépéseinek bemutatása, a kapcsolódó zöldmezős beruházás forrásösszetételének és megtérülésének vizsgálata, valamint a vállalkozás rövid és hosszú távú gazdasági viszonyainak értékelése. Feltevésem szerint a beruházás a tudatos tervezési folyamat és a korszerű technológiák alkalmazásának köszönhetően tíz éven belül biztonsággal megtérül. Az általános célkitűzésem megvalósításához az elemzést konkrét lépésekre bontottam le. A mezőgazdasági vállalkozás belső adottságait (erősségek, gyengeségek) és külső feltételeit (lehetőségek, veszélyek) a swot-elemzés módszerével foglaltam össze. Az elemzést a gyengeségek és veszélyek elleni intézkedésekkel is kiegészítettem. Mivel a vállalkozás önereje nem volt elég a beruházás végrehajtásához, ezért a számításoknál figyelembe kellett vennem az uniós forrásból származó pénzösszegeket is. Az uniós pályázat kapcsán tanulmányoztam az elnyert támogatás teljesítéséhez kapcsolódó feltételrendszer megvalósíthatóságát. A termelés folytonosságának biztosítása érdekében megvizsgáltam a választott értékcsökkenési leírás megfelelőségét. A termelés rövidtávú gazdasági helyzetének és társadalmi, gazdasági, politikai környezetének elemzésén túl elvégeztem a fejlesztés hosszú távú gazdaságossági vizsgálatát is, amihez dinamikus beruházás-gazdaságossági számításokat (nettó jelenérték számítás, dinamikus megtérülési idő, forgási sebesség, belső megtérülési ráta) végeztem. A számítások alapján bebizonyosodott, hogy a vállalkozás megvalósításának a jelenlegi gazdasági és pénzügyi viszonyok mellett van létjogosultsága. A pénzügyi számítások alapján a beruházás már a nyolcadik évben megtérül és ezután még plusz hozamok is várhatók. A belső kamatláb jóval az előzetes elvárások felett alakul. Bár a gazdaság nem nélkülözi a nehézségeket és a kockázatokat, a tulajdonos megfelelő intézkedési tervvel rendelkezik ezek áthidalására. A tervezett pénzáramok biztosítják az elavulás után a technológia cseréjéhez szükséges tőkét, ami azt mutatja, hogy a vállalkozás hosszú távon is fenntartható.